2008
DOI: 10.1017/s0025315408000763
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of the Pelagos Sanctuary (north-western Mediterranean Sea) into hotspots and coldspots of cetacean distributions

Abstract: This study used Monte Carlo methods to generate simulations that considered the effort distribution to determine the locations of significant aggregations of cetacean sightings inside the northern Pelagos Sanctuary (north-western Mediterranean Sea). For three years, monitoring has been conducted from five motor vessels covering about 30,050 km. The most frequently encountered species were the striped dolphin Stenella coeruleoalba representing 64.7% of all sightings, the fin whale Balaenoptera physalus (17.0%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…In the Pelagos Sanctuary, Cuvier's beaked whale exploits the upper and lower slopes along the Ligurian−Provençal coast, at depths ranging from 1000 to 2500 m (Azzellino et al 2008, Moulins et al 2008, showing preference for areas with complex topography (Moulins et al 2007, Gannier & Epinat 2008, Azzellino et al 2012. Similar habitat preferences have been found for the sperm whale, whose preferred habitat lies in the canyons in the slope area (Gannier et al 2002, Moulins et al 2008, Praca et al 2009, Azzellino et al 2012.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…In the Pelagos Sanctuary, Cuvier's beaked whale exploits the upper and lower slopes along the Ligurian−Provençal coast, at depths ranging from 1000 to 2500 m (Azzellino et al 2008, Moulins et al 2008, showing preference for areas with complex topography (Moulins et al 2007, Gannier & Epinat 2008, Azzellino et al 2012. Similar habitat preferences have been found for the sperm whale, whose preferred habitat lies in the canyons in the slope area (Gannier et al 2002, Moulins et al 2008, Praca et al 2009, Azzellino et al 2012.…”
Section: Introductionmentioning
confidence: 53%
“…Previous research carried out in the Pelagos Sanctuary revealed a longitudinal segregation be tween the 2 species, with a higher presence of sperm whale in the northwestern part of the area, while Cuvier's beaked whale is more common in the Gulf of Genoa area (Gannier et al 2002, Moulins et al 2008. These opposite longitudinal gradients in the distribution of the 2 species might allow the spatial differentiation of habitat.…”
Section: Environmental Variablesmentioning
confidence: 88%
See 3 more Smart Citations